Recent advances in the identification and authentication methods of edible bird's nest. (October 2017) - Lee, Ting Hun; Wani, Waseem A.; Koay, Yin Shin; Kavita, Supparmaniam; Tan, Eddie Ti Tjih; Shreaz, Sheikh
Abstract: Edible bird's nest (EBN) is an expensive animal bioproduct due to its reputation as a food and delicacy with diverse medicinal properties. One kilogram of EBN costs 6000 in China. EBN and its products are consumed in mostly Asian countries such as China, Hong Kong, Taiwan, Singapore, Malaysia, Indonesia, Vietnam and Thailand, making up almost 1/3 of world population. The rapid growth in EBN consumption has led to a big rise in the trade scale of its global market. Presently, various fake materials such as tremella fungus, pork skin, karaya gum, fish swimming bladder, jelly, agar, monosodium glutamate and egg white are used to adulterate EBNs for earning extra profits. Adulterated or fake EBN may be hazardous to the consumers. Thus, it is necessary to identify of the adulterants. Several sophisticated techniques based on genetics, immunochemistry, spectroscopy, chromatography and gel electrophoresis have been used for the detection of various types of adulterants in EBN. This article describes the recent advances in the authentication methods for EBN. Different genetic, immunochemical, spectroscopic and analytical methods such as genetics (DNA) based techniques, enzyme-linked immunosorbent assays, Fourier transform infrared and Raman spectroscopic techniques, and chromatographic and gel electrophoretic methods have been discussed. Besides, significance of the reported methods that might pertain them to applications in EBN industry has been described. Finally, efforts have been made to discuss the challenges and future perspectives of the authentication methods for EBN. Graphical abstract: Highlights: Discussion of recent advances in the authentication methods of EBN. Applications of genetic, immunochemical, spectroscopic, chromatographic, gel electrophoretic for EBN adulterants detection. Significance of the methods that pertain them to applications in EBN industry. The challenges and future outlooks of the identication and authentication methods.